2011
DOI: 10.1371/journal.pone.0022619
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Dynamics Model for the Speract-Activated Ca2+ Signaling Network Relevant to Sperm Motility

Abstract: Understanding how spermatozoa approach the egg is a central biological issue. Recently a considerable amount of experimental evidence has accumulated on the relation between oscillations in intracellular calcium ion concentration ([Ca]) in the sea urchin sperm flagellum, triggered by peptides secreted from the egg, and sperm motility. Determination of the structure and dynamics of the signaling pathway leading to these oscillations is a fundamental problem. However, a biochemically based formulation for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 61 publications
3
51
0
Order By: Relevance
“…Furthermore, we recently found that the highly specific blocker of CaKC Iberiotoxin at 100 nM increases the period between the [Ca 2+ ] i fluctuations triggered by speract in S. purpuratus spermatozoa (Espinal et al, 2011). If CaCC and/or CaKC channels participate in the speract signaling pathway, they would open in response to Ca 2+ entry, leading to influx of Cl 2 and/or efflux of K + , and therefore V m hyperpolarization (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Furthermore, we recently found that the highly specific blocker of CaKC Iberiotoxin at 100 nM increases the period between the [Ca 2+ ] i fluctuations triggered by speract in S. purpuratus spermatozoa (Espinal et al, 2011). If CaCC and/or CaKC channels participate in the speract signaling pathway, they would open in response to Ca 2+ entry, leading to influx of Cl 2 and/or efflux of K + , and therefore V m hyperpolarization (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…In a previous work (Espinal et al, 2011), we developed a discrete logical model to describe the temporal dynamics of the speract-activated signaling network in the S. purpuratus sea urchin sperm flagellum. Encouraged by the experimental validation of the model predictions (Espinal et al, 2011), here we used this model to investigate in silico the effect on the [Ca 2+ ] i oscillations of altering the NFAsensitive channels present in the sea urchin sperm flagellum.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 3 more Smart Citations